Changes in chemical properties of three soil types after application of biochars and organic fertilizers for two years - Frengky Umbu Kolambani; Widowati Widowati (Brawijaya University, 2022)
This study assessed organic matter, N, P, and K contents in three soil types after the application of biochars and organic fertilizers for two years. The experiment was arranged in a nested design with two factors. Three types of biochar and two types of organic fertilizer were used singly or in combination on three soil types. Among the treatments, the application of tobacco processing waste biochar on Inceptisol and rice husk biochar plus manure on Entisol resulted in the highest soil organic matter and total nitrogen contents. The highest phosphorus content was observed from rice husk biochar treatment on Inceptisol and from rice husk biochar+manure treatment on Entisol and Litosol. The highest K content in Inceptisol and Litosol occurred with each biochar treated rice husk biochar+manure treatment. The highest K content in Inceptisol and Litosol was observed in each tobacco waste biochar+compost treatment and in compost treatment only, respectively.